Effect of Dietary Vitamin D3 and Ultraviolet B Light on Growth Performance, Blood Serum Parameters, Gut Histology, and Welfare Indicators of Broilers - Ogbonna, Amarachi Chijioke; Chaudhry, Abdul Shakoor; Asher, Lucy (Frontiers in Animal Science, 2022)
Stressors are commonly encountered by all farmed species, including chickens, but the impact of these stressors on the animal and their productivity can be influenced by the environmental conditions in which they are kept. This study investigated the effects of dietary vitamin D3 (vitD3) and ultraviolet light (UVB) on growth performance, organ weight, serum corticosterone levels (CORT), serum 25-hydroxy vitamin D (25-OH-D3) status, gut histology, and welfare indicators of broiler chickens challenged with social isolation stress. One day (d) old Ross 308 broiler chicks (n=192) were individually weighed, wing-tagged, and allocated to non-isolated (control) and isolated groups; control birds were never isolated, while isolated birds were subjected to regular sessions of social isolation for about 15‐minutes periods over the course of 3 d a week for 2 weeks starting from d 10 (1.30 hours total exposure) with inter treatment interval of 48 hours. Birds were treated with either dietary vitD3 at 4000 IU/kg (HD) or UVB light (UVB). The UVB lamp (24 Watt 12% UVB D3, 55 cm) with wavelength: 280-315 nm, intensity; 28.12 µW/cm2 hung 50 cm above the substrate was used for the broilers in all the treatment groups but were filtered to remove UVB in the HD group. Growth performance measure; body weight gain, feed intake, and feed conversion ratio were estimated at the end of starter (day 10), grower (day 24), and finisher periods (day 38). Broilers were feather and gait scored to measure welfare at 22/35 and 24/37 days of age, respectively. The selected birds were weighed and euthanized to obtain serum to determine 25-OH-D3 and CORT levels, GIT weights, and gut histology. Subjecting the birds to 2-week social isolation (for fifteen minutes, three times per week) increased CORT levels but did not alter GP and 25-OH-D3 levels of broilers. However, UVB-treated broilers demonstrated better welfare, duodenal absorptive capacity, and reduced FCR compared to HD chickens. Results suggest some beneficial effects of UVB lighting on welfare indicators and the potential to support early life growth of commercial broilers reared indoors, which are often challenged with stressors